Promotif dan Preventif Bagi Klien Diabetes di Puskesmas Cipto Mulyo Malang terhadap Resiko Kecelakaan Dalam Berkendaraan - Zaqqi Ubaidillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
DM clients will continue to carry out daily activities like normal people in general, including driving activities. The most trips made by DM patients are to work, fill spare time, recreation and health services. However, there are dangers that can cause accidental diabetic clients, including blood glucose disorders, decreased visual acuity and neuropathy. The risk of accidents for diabetic clients is high. The purpose of this service is that this activity is expected to be able to increase understanding for diabetic clients and prevent the risk of accidents for DM clients. The sampling technique in this service uses purposive sampling. Diabetic clients who participate in this service generally experience problems in driving. The perceived disturbances include frequent fatigue, visual disturbances, decreased response, hyperglycemia and hypoglycemia. It is necessary to have periodic checks in collaboration with the puskesmas regarding this matter. Thus, diabetic clients who are still actively driving are prevented from having accidents.